PENGARUH PEMBELAJARAN BERBASIS PROJEK DAN MOTIVASI MAHASISWA DALAM PERSIAPAN DUNIA KERJA - Elistya Rimawati; Ari Wibowo; Wawan Laksito Yuly Saptomo (ITB AAS Indonesia Surakarta, 2025)
The evolving world of work in the era of globalization and the Industrial Revolution 4.0 demands that students master not only theoretical knowledge but also basic 21st-century skills. Students and universities need to prepare graduates to compete in the workforce. Project-based learning is one model that can be applied in learning because it offers great potential in creating meaningful experiences for students as they enter the workforce. Student motivation is also necessary to prepare work-ready graduates. The results of the analysis using SEM PLS Project Based Learning (PjBL) and student motivation significantly have a positive effect on student work readiness, where PjBL (X₁) with a path coefficient of 0.387 (p-value 0.000 <0.05) is proven to be effective in building technical competencies, practical skills such as problem-solving, collaboration, communication and project management, as well as developing creativity through the stages of planning, making, presenting, and evaluating products, while motivation (X₂) with a higher path coefficient of 0.420 (p-value 0.000 <0.05) acts as an internal driver that increases students' perseverance, initiative, and psychological readiness in facing the world of work. The synergy of PjBL and Motivation creates a strong combination effect in increasing work readiness, with an R² value of 0.467 indicating that most of the variance in work readiness can be explained by these two exogenous variables. Keywords : Project Based Learning, motivation, work readiness, SEM PLS